2022
DOI: 10.1111/rec.13635
|View full text |Cite
|
Sign up to set email alerts
|

Does revegetation cause soil microbiota recovery? Evidence from revisiting a revegetation chronosequence 6 years after initial sampling

Abstract: The global biodiversity and land degradation crises have brought about an urgent need and great demand for restoration actions. However, restoration outcomes are often less than ideal, indicating a need for improved restoration practices. Soil microbiota are extremely diverse and functionally important and should be further considered in restoration. However, despite their importance, there remains a gap in understanding of how soil microbiota respond following native plant revegetation. Several studies have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…This environmentally driven spatial variation of soil microbial communities highlights the need for appropriate experimental designs that limit spatial confounders where practicable or address their ecological implications. Furthermore, to experimentally test cause-effect relationships in a rehabilitation context, either experiments need to be embedded into rehabilitation sites (Gellie et al 2018) or longitudinal studies need to be done to conclusively ascertain temporal changes in soil microbiota (Lem et al 2022). Also, to investigate any potential return of key bacterial-mediated ecological functions, future studies should incorporate shotgun metagenomic data to directly ascertain changes in functional gene abundances as inferring any functional changes from 16s data alone is problematic (Sun et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This environmentally driven spatial variation of soil microbial communities highlights the need for appropriate experimental designs that limit spatial confounders where practicable or address their ecological implications. Furthermore, to experimentally test cause-effect relationships in a rehabilitation context, either experiments need to be embedded into rehabilitation sites (Gellie et al 2018) or longitudinal studies need to be done to conclusively ascertain temporal changes in soil microbiota (Lem et al 2022). Also, to investigate any potential return of key bacterial-mediated ecological functions, future studies should incorporate shotgun metagenomic data to directly ascertain changes in functional gene abundances as inferring any functional changes from 16s data alone is problematic (Sun et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Barber et al 2017; Gellie et al 2017), while others have found either that recovery had stalled (e.g. Farrell et al 2020 b ; Lem et al 2022) or recovery is dependent on organism or topsoil handling methods (Van Der Heyde et al 2020). This presents a problem since soil microbiota are highly diverse and functionally important ecosystem components and therefore understanding their ecology and responses to both impacts and restoration or rehabilitation is integral to ecosystem restoration (Cameron et al 2018; Delgado‐Baquerizo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil microbiota are fundamentally linked to the restoration of degraded ecosystems; therefore, DNA‐based methods to characterise shifts in soil bacterial community composition have been developed to track restoration progress. Successful restoration of postagricultural landscapes back to biodiverse, functional, and self‐sustaining ecosystems is often hampered by legacies that linger from decades of unsustainable land use (Lem et al ., 2022; Peddle et al ., 2023). Developed from restoration chronosequence study datasets, a new ‘rehabilitation trajectory assessment’ (Liddicoat et al ., 2022) offers promise to help monitor and inform adaptive management practices and predict the ecological progress of restoration sites towards reference states (Craig Liddicoat, Flinders University).…”
Section: How Can Soil Microbial Communities Advance the Restoration O...mentioning
confidence: 99%
“…Natural regeneration, a common restoration practice without direct human interference, could increase microbial network complexity (Morrien et al, 2017). Meanwhile, active revegetation with a change in plant community composition significantly increases microbial diversity and affects soil microbial community reorganization primarily due to the increase of soil nutrient availability (Araujo et al, 2014; Lem et al, 2022; Ren et al, 2018; Wang et al, 2022; Yan et al, 2019). On the other hand, soil functional fungi including fungal decomposers, plant pathogens and mycorrhizal fungi can help plants withstand environmental challenges and maintain ecosystem functions (de Vries et al, 2020; Wagg et al, 2021; Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%